Using propositional logic to prove that each argument is valid.If Jose took the jewelry or Mrs. Krasov lied, then a crime was committed. Mr. Kraso was not in town. If a crime was committed, then Mr. Krasov was in town. Therefore Jose did not take the jewerly. Use letters J, L, C, T.So for this question, I am very confused and would appreciate any help offerd.

Respuesta :

Answer:

Step-by-step explanation:

We will first translate the situation to propositional logic. First, some notation is needed: [tex]\lor[/tex] is the or logical operation and [tex]\implies[/tex] is the symbol for logical implication. Define the following events:

J: Jose took the jewelry. L: Mrs Krasov lied, C: a crime was committed. T: Mr Krasov  was in town.

We will symbol the propositions in logical symbols. Recall that [tex]\neg[/tex] means negation

If Jose took the jewelry or Mrs. Krasov lied, then a crime was committed: [tex]J\lor L \implies C[/tex]

Mr. Krasov was not in town: [tex]\neg T[/tex]

If a crime was committed, then Mr. Krasov was in town: [tex]C\implies T[/tex]

We want to check if the conclusion Jose did not take the jewerly: [tex]\neg J[/tex] can be deduced from the premises.

First, recall the following:

- if [tex] a\implies b[/tex] and a is true, then b is true.

- [tex] a\implies b[/tex] is logically equivalent to [tex]\neg b \implies a[/tex]

Coming back to the problem, we have the following premises

[tex]J\lor L \implies C, \neg T, \neg T \implies \neg C, \neg C \implies \neg(J\lor L)[/tex]

where the equivalence for the logical implication was applied. REcall that the negation of an or  statement is g iven by

[tex] \neg( a \lor b ) = \neg a \land \neg b [/tex] where [tex] \land[/tex] is the and logical operator.

USing this, we get the premises

[tex]J\lor L \implies C, \neg T, \neg T \implies \neg C, \neg C \implies \neg J\land \neg L[/tex]

Since [tex]\neg T[/tex], by having [tex]\neg T \implies \neg C[/tex], then it must be true that [tex]\neg C[/tex]. Since [tex]\neg C \implies \neg J\land \neg L[/tex], then it must be true that [tex] \neg J\land \neg L[/tex]. This final conclusion implies that it is true that [tex]\neg J[/tex] which is the statement that Jose did not take the jewelry.